(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Benign Paroxysmal Positional Vertigo (BPPV) is one of the most frequent vestibular disorder. It is characterized by recurrent spells of vertigo associated with certain head movements such as turning the head to right or left, getting out of bed, looking up and bending down. Objectives: The aim of this study was to compare the efficacy of treatment by the Epley maneuver with medicine and medicine (betahistine) only for benign paroxysmal positional vertigo. Materials and Methods: Fifty six patients with benign paroxysmal positional vertigo were randomly divided in two groups. One group was treated with Epley maneuver wth medicine as case and other group with only medicine (betahistine) as control. Results: At the end of first week who were treated with Epley maneuver with medicine, 24 (85.71%) patients recovered and 27 (96.42%) were recovered at second week and all the 28 (100%) were found recovered at end of third week. Whereas, who treated with betahistine only 7(25.00%) recovered at end of first week 22 (78.58%) recovered at second week, 25 (89.29%) recovered at third week and all the 28 (100%) were at end of fourth week. Who received only medical therapy needed one more extra visit than case patients Conclusion: Treatment of BPPV with the Epleys manouvre with medicine resulted in early better and improvement of symptoms than with medicine alone. Bangladesh J Otorhinolaryngol; April 2018; 24(1): 3-7